Improving Students’ Reading Comprehension by Using Graded Reading Material - Dahlina, Ulinuha; Fadilah, Nurul (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2022)
This research was conducted in order to improve students’ reading comprehension at the twelfth-grade students of SMAN 1 Kramatwatu which consisted of 33 students’ consisting of 16 males and 21 females by using Graded Reading Materials. This research used a Classroom Action Research (CAR) which was conducted to solve the students’ problem in English reading. The researcher employed two cycles, each cycle consisted of planning, acting, observing and reflecting. The data were gathered through qualitative and quantitative data. The qualitative data were obtained by analyzing the test. Then, quantitative data were obtained by analyzing the observation checklist. The finding of the research indicated that the implementation of Graded Reading Materials was successful since the criteria of success were achieved. The first cycle was 24.24% of students could exceed the target score based on the Standard Minimum Score, but 75.75% of students did not achieve the target score. The second cycle showed that 100% of students had already achieved the target score based on the Standard Minimum Score. The results of observation checklist showed that through Graded Reading Materials, the students were more creative and confident in the classroom especially in reading activity. Based on the finding mentioned previously, the researcher suggests that English teacher could implement Graded Reading Materials in teaching reading in order to improve students’ ability in learning English reading. Further, the researcher assumes that the more students read English texts, the better their reading skill will be.